The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.3109/10826088609083536
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Abuse in College Students. I. A Review of Individual and Personality Correlates

Abstract: This review of alcohol use and abuse in college students presents a summary of the relationships between college student alcohol use and demographic and individual characteristics. A summary of the findings suggests two distinct patterns of alcohol use. For some demographic groups, heavy drinking may be most associated with personal problems, while for others it may be more associated with social and environmental factors. Suggestions for future research of this important issue are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 43 publications
2
68
0
Order By: Relevance
“…However, the enhanced sensitivity was specific to self-report measures; d-amphetamine effects on cardiovascular and performance measures were not different between groups. High novelty or sensation-seeking status is associated with an increased frequency and amount of drug use (Brennan et al 1986;Wills et al 1994Wills et al , 1995 and increased risk for the development of drug abuse and dependence (Hawkins et al 1992;Huba et al 1981). The results of this study suggest that escalating patterns of drug use and the development of problems associated with that use among high impulsive high sensation seekers might be due, in part, to increased sensitivity to the reinforcing effects of drugs.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the enhanced sensitivity was specific to self-report measures; d-amphetamine effects on cardiovascular and performance measures were not different between groups. High novelty or sensation-seeking status is associated with an increased frequency and amount of drug use (Brennan et al 1986;Wills et al 1994Wills et al , 1995 and increased risk for the development of drug abuse and dependence (Hawkins et al 1992;Huba et al 1981). The results of this study suggest that escalating patterns of drug use and the development of problems associated with that use among high impulsive high sensation seekers might be due, in part, to increased sensitivity to the reinforcing effects of drugs.…”
Section: Discussionmentioning
confidence: 69%
“…The personality dimension of novelty or sensation seeking is associated with the initiation of drug use and the frequency and amount of drug use among adolescents and young adults (Brennan et al 1986;White et al 2005;Wills et al 1994Wills et al , 1995. Furthermore, individuals with these personality traits are at increased risk for the development of drug abuse and dependence (Hawkins et al 1992;Huba et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of using alcohol as escape is worrisome, for research shows heavier drinkers use alcohol more for that reason, whereas lighter drinkers typically use alcohol for pleasure (Brennan, Walfish, and AuBuchon 1986).…”
mentioning
confidence: 99%
“…Many researchers have found that drinking alcohol to cope with problems is more likely to lead to abusive drinking than is social drinking (Cahalan et al, 1969;Cooper et al, 1988;Farber et al, 1980;Johnson et al, 1985). There is also evidence, however, that social motives for consuming alcohol can lead to heavy drinking (Brennan, Walfish, & AuBuchon, 1986;Ratliff & Burkhart, 1984). For example, Brennan et al (1986), in their review of the longitudinal literature on college student drinkers, found that heavy drinkers who drank for social reasons were more prone to later problem drinking than heavy drinkers who drank to cope with personal problems.…”
mentioning
confidence: 99%
“…There is also evidence, however, that social motives for consuming alcohol can lead to heavy drinking (Brennan, Walfish, & AuBuchon, 1986;Ratliff & Burkhart, 1984). For example, Brennan et al (1986), in their review of the longitudinal literature on college student drinkers, found that heavy drinkers who drank for social reasons were more prone to later problem drinking than heavy drinkers who drank to cope with personal problems. Thus, there is evidence that both social and coping motives for consuming alcohol can lead to heavy drinking.…”
mentioning
confidence: 99%